2018
DOI: 10.3892/etm.2018.7138
|View full text |Cite
|
Sign up to set email alerts
|

Novel triazole analogs of apigenin‑7‑methyl ether exhibit potent antitumor activity against ovarian carcinoma cells via the induction of mitochondrial‑mediated apoptosis

Abstract: Ovarian cancer is one of the main causes of cancer-associated mortality across the world. Currently, ovarian cancer is mainly treated with chemotherapy. However, ovarian cancer is detected at advanced stages and chemotherapy has numerous side effects. In addition, the results of current chemotherapy on the treatment of ovarian cancer are less than satisfactory. Therefore, there is an urgent need to develop novel and more viable chemotherapeutic agents that can be used to treat ovarian cancer. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Qi et al. 67 found that novel triazole analogs of apigenin-7-methyl ether exhibit potent antitumor activity against ovarian carcinoma cells via the induction of mitochondria-mediated apoptosis. Of all the derivatives, the derivative 14 ( Figure 6 ) exhibited significant and dose-dependent anticancer activity against the SKOV3 ovarian cancer cell line.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Qi et al. 67 found that novel triazole analogs of apigenin-7-methyl ether exhibit potent antitumor activity against ovarian carcinoma cells via the induction of mitochondria-mediated apoptosis. Of all the derivatives, the derivative 14 ( Figure 6 ) exhibited significant and dose-dependent anticancer activity against the SKOV3 ovarian cancer cell line.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Flavone derivatives 37a – 37g ( Figure 13 ) of apigenin-7-methyl ether were synthesized by CuAAC reaction between O -propargylated flavone and substituted azides. These compounds exhibited antiproliferative activity against ovarian cancer cell lines SKOV3, OVCAR-3 and Caov-3 (10 < IC 50 < 40 µM) [ 78 ]. Hybrid 37a showed the highest antiproliferative activity against all cancer cells (IC 50 = 10, 15 and 20 µM for SKOV3, OVCAR-3 and Caov-3, respectively) and was found to induce apoptosis on SKOV3 cells through ROS-mediated alterations in mitochondrial membrane potential (MMP), and modulated the expression of Bcl-2 and Bax proteins [ 78 ].…”
Section: 123-triazole-linked Flavonoid Hybrids With Antitumor Activitymentioning
confidence: 99%
“…Rao et al reported that the flavone/imidazole-triazole derivative G3 could exert moderate antiproliferative activity against MCF-7 cancer cells (IC 50 = 17.9 μ M) ( Rao et al, 2018 ). Chen et al reported that apigenin-triazole G4 could exert inhibitory activity against SKOV-3 cells (IC 50 = 10 μ M) ( Qi et al, 2018 ). Mechanistic studies indicated that G4 could promote the level of cellular reactive oxygen species (ROS) and reduce the mitochondrial membrane potential, thereby inducing the apoptosis of SKOV-3 cells.…”
Section: Click Chemistry-based Modification Of Phenylpropanoidsmentioning
confidence: 99%